Relatório de Estágio Profissional "O Sonho de ser Professora: Fator chave para o envolvimento no estágio" - Cláudia Manuela da Silva Henriques (2017)
The current report is part of the second cycle of higher studies leading to the master's degree in Physical Education Teaching in the Basic and Secondary Education, of the Faculty of Sport of the University of Porto and aims to analyze and illustrate the path taken by a preservice teacher along her practicum training. This document describes in a reflective way, not only all the experiences, the learning and decision-making processes but also the results achieved by the preservice teacher. The practicum training was held at a school of the Aveiro district, in a group of three preservice teacher, the cooperating teacher and the faculty supervisor. The preservice teacher was responsible for the teaching of a twelfth year class of Visual Arts and had other teaching experiences in the first and second Cycles of Basic Education. In terms of structure, the document includes five central chapters: the first, "Introduction" which contextualizes the document. The second refers to the "Biographic Context", reflecting academic and sports experiences, reasons for professional choice, as well as the contrast between expectations and the reality of the preservice teacher. In the third chapter "Professional Practice Framework" are characterized the legal and institutional context of the practicum training, the praticum group and the assigned classes. The fourth chapter refers to " Professional Practice implementation", which is subdivided into three performance areas. Area 1, "Organization and Management of Teaching and Learning", encompasses the concept, planning, implementation and evaluation; Area 2, "Participation in School and Relationship with Community" and Area 3, "Professional Development". In this chapter, is present the research study that focus the theme of functional training in the context of Physical Education classes. The fifth and final chapter presents final considerations and expectations for the future.